Pengaruh Kerusakan Jalan Terhadap Nilai Ekonomi Penanganan Konstruksi Jalan - Mangidi, Suhardin; Sunaryo, Sunaryo; Sulaiman, Sulaiman; Sufrianto, Sufrianto (Universitas Sulawesi Tenggara, 2021)
This study aims to analyze the value of the Pavement Condition Index (PCI), analyze the amount of the budget needed to deal with road damage, and analyze the value of the influence between the value of the PCI and the budget for road repair on the Gunung Jaya - Poli- Polia road section. The results of this study indicate that the pavement condition index (PCI) of Gunung Jaya - Poli-Polia Road is 52.5 in the medium category. The total budget required to deal with the damage to the Gunung Jaya - Polia-Polia road is Rp. 12,085,500,000.00. PCI value affects the budget plan of 21.5%.